Das Wunder von Europa läßt noch auf sich warten: Zu Lage und Perspektiven der europäischen Linken nach der neoliberalen Gegenreform - Wolf, Frieder Otto (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
The European Left will have to undergo a deep sea-change, in order to really come into existence. It is attempted to outline the underlying trends of the post-neoliberal situation, to grasp the creativity of European popular struggles, and to describe the strategical tasks by the solution of which another new European left could begin to create itself, in changing the societal development of European integration.